Elementary Science Teacher Educators Learning Together: Catalyzing Change With Educative Curriculum Materials and Vignette Writing - Asim, Sumreen; Davis, Jeni; Kinskey, Melanie; Lavender, Heather; Murray, Jaclyn; Obery, Amanda; Sherwood, Carrie-Anne; Voss, Sarah (Innovations in Science Teacher Education, 2023)
In this article, we describe a professional learning community (PLC) for science teacher educators that supported changes in pedagogy through educative curriculum materials and vignette writing. The PLC was convened as part of a grant-supported project to build preservice elementary teachers’ content knowledge for matter using educative curriculum materials. PLC members collaborated with one another over an academic year to learn about and discuss implementing curricular materials in their respective science teacher education courses. Due to the collaborative nature of the PLC, members were able to engage in sensemaking collectively around challenges of practice through vignette writing. The process of writing vignettes within the PLC allowed for productive reflection around content knowledge for matter and science teaching practices, ultimately, advancing preservice teachers’ learning about teaching elementary science.